Important Role Of Operating System In Computer Network Connection - Raditya Arya Darmawan; Weni Gurita Aedi (Dinasti Publisher, 2025)
Operating systems play a crucial role in supporting network management, ensuring that devices are properly connected and security protocols are effectively implemented. As the adoption of Internet of Things (IoT) devices increases, efficient operating systems facilitate integration and communication between these devices, which in turn increases efficiency and automation in various sectors, and has a real positive impact on our lives today. This study aims to describe the important role of operating systems in managing computer network connections. The research method used is qualitative descriptive, with data obtained from various sources, including e-books and journal articles related to operating systems and computer networks. Journal articles on network management, protocols, security, and performance, as well as research reports and case studies that discuss the role of operating systems in computer network connections. Based on the results of the data analysis, computer network connections are currently experiencing rapid progress with various innovations in network security technology also being a major focus, with technologies such as encryption, firewalls, and VPNs to protect data from cyber threats. However, without an efficient operating system, management and communication between devices in an IoT network can be hampered. The operating system is responsible for ensuring that devices can be properly connected, as well as managing the necessary security protocols.